2001
DOI: 10.1021/ja010942j
|View full text |Cite
|
Sign up to set email alerts
|

Negative-Ion Photoelectron Spectroscopy, Gas-Phase Acidity, and Thermochemistry of the Peroxyl Radicals CH3OO and CH3CH2OO

Abstract: Methyl, methyl-d(3), and ethyl hydroperoxide anions (CH(3)OO(-), CD(3)OO(-), and CH(3)CH(2)OO(-)) have been prepared by deprotonation of their respective hydroperoxides in a stream of helium buffer gas. Photodetachment with 364 nm (3.408 eV) radiation was used to measure the adiabatic electron affinities: EA[CH(3)OO, X(2)A' '] = 1.161 +/- 0.005 eV, EA[CD(3)OO, X(2)A' '] = 1.154 +/- 0.004 eV, and EA[CH(3)CH(2)OO, X(2)A' '] = 1.186 +/- 0.004 eV. The photoelectron spectra yield values for the term energies: Delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
129
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 58 publications
28
129
2
1
Order By: Relevance
“…A number of workers have computed the difference in energy between the cis and trans forms. Braams and Yu (2008) [146] using the density functional method (DFT) HCTH computed that the cis form was 4.6 kJ mol −1 higher with barrier-to-rotation of 8. potential to produce a torsional potential of 132 cm −1 that roughly agrees with the experimental torsional frequency of 129 cm −1 . Varandas (2012 [143,222] using CCSD(T) and MRCI-Q methods with cc-pVnZ basis sets extrapolated to the complete basis set limit and including higher order corrections calculated the cis form to be (0.5 to 0.6) kJ/mol higher with a barrier-to-rotation of about (3.3 to 4.8) kJ mol −1 .…”
Section: Sumamentioning
confidence: 99%
“…A number of workers have computed the difference in energy between the cis and trans forms. Braams and Yu (2008) [146] using the density functional method (DFT) HCTH computed that the cis form was 4.6 kJ mol −1 higher with barrier-to-rotation of 8. potential to produce a torsional potential of 132 cm −1 that roughly agrees with the experimental torsional frequency of 129 cm −1 . Varandas (2012 [143,222] using CCSD(T) and MRCI-Q methods with cc-pVnZ basis sets extrapolated to the complete basis set limit and including higher order corrections calculated the cis form to be (0.5 to 0.6) kJ/mol higher with a barrier-to-rotation of about (3.3 to 4.8) kJ mol −1 .…”
Section: Sumamentioning
confidence: 99%
“…Methyl hydroperoxide, CH 3 OOH, has been the subject of numerous publications [20][21][22][23][24] since a comprehensive review by Dorofeeva et al in 2001. 25 They concluded that ∆H f (298.15K) ) -139.0 ( 5.0 kJ mol -1 represented the best estimate from values which ranged from -122 to -143 kJ mol -1 .…”
Section: Alkyl Hydroperoxidesmentioning
confidence: 99%
“…b Ref. [36] c Ref. [37] of m for H-atom abstractions is governed [9] by the species of lowest I P , which is the 1,4-pentadie-3-yl radical, and highest electron affinity, which is the tert-butyl peroxyl radical.…”
Section: Resultsmentioning
confidence: 99%